Pulmonary Embolism as the First Manifestation of Multiple Myeloma - N. Vallianou; V. Lazarou; J. Tzangarakis; R. Barounis; E. Sioula (Case Reports in Medicine)
Multiple myeloma is considered a hypercoagulable state due to several mechanisms such as the increased IL-6 and immunoglobulins production, the defective fibrinolytic mechanism, and the acquired resistance to activated protein C that are involved in the pathogenesis and clinical futures of the disease. We describe a case of a female patient who presented to the hospital with pulmonary embolism as the first manifestation of the hypercoagulability of multiple myeloma.